Halal Tourism from the Perspective of the Quran: An Exploration of the Meaning of Riḥlah According to Ash-Shaʻrāwī and Its Implications for Muslim Travel Ethics - Muhammad Fakih Hasibuan; Sukiman Sukiman; Muhammad Roihan Nasution (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
The growing trend of Muslim travel to various global destinations necessitates the concept of halal tourism, which prioritises not only the fulfilment of Islamic law but also Islamic ethical and spiritual values. However, the implementation of halal tourism has tended to be reductive, focusing primarily on halal food and prayer facilities, without exploring more substantive Quranic dimensions. This study aims to explore the meaning of riḥlah in the Quran based on Ash-Shaʻrāwī’s interpretation and examine its implications for contemporary Muslim travel ethics. Using a qualitative method with a thematic approach and analysis of Ash-Shaʻrāwī’s thematic interpretations, data were collected from tafsir books, supporting literature, and secondary sources on halal tourism. The results show that riḥlah, from the Ash-Shaʻrāwī perspective, is not merely a physical activity of moving from one place to another, but a spiritual and epistemological process of knowing God through His signs in nature. Riḥlah also has social, economic, and educational functions, emphasising morality, responsibility, and self-reflection. In the context of halal tourism, these values form the basis for establishing a responsible, environmentally conscious, and respectful Muslim travel ethic.